Solve for u -3u+1/3=-5/4u-4/3

Math
-3u+13=-54u-43
Simplify each term.
Tap for more steps…
Combine u and 54.
-3u+13=-u⋅54-43
Move 5 to the left of u.
-3u+13=-5u4-43
-3u+13=-5u4-43
Move all terms containing u to the left side of the equation.
Tap for more steps…
Add 5u4 to both sides of the equation.
-3u+13+5u4=-43
To write -3u as a fraction with a common denominator, multiply by 44.
-3u⋅44+5u4+13=-43
Combine -3u and 44.
-3u⋅44+5u4+13=-43
Combine the numerators over the common denominator.
-3u⋅4+5u4+13=-43
Simplify each term.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Factor u out of -3u⋅4+5u.
Tap for more steps…
Factor u out of -3u⋅4.
u(-3⋅4)+5u4+13=-43
Factor u out of 5u.
u(-3⋅4)+u⋅54+13=-43
Factor u out of u(-3⋅4)+u⋅5.
u(-3⋅4+5)4+13=-43
u(-3⋅4+5)4+13=-43
Multiply -3 by 4.
u(-12+5)4+13=-43
Add -12 and 5.
u⋅-74+13=-43
u⋅-74+13=-43
Move -7 to the left of u.
-7⋅u4+13=-43
Move the negative in front of the fraction.
-7u4+13=-43
-7u4+13=-43
-7u4+13=-43
Move all terms not containing u to the right side of the equation.
Tap for more steps…
Subtract 13 from both sides of the equation.
-7u4=-43-13
Combine the numerators over the common denominator.
-7u4=-4-13
Subtract 1 from -4.
-7u4=-53
Move the negative in front of the fraction.
-7u4=-53
-7u4=-53
Multiply both sides of the equation by -47.
-47⋅(-7u4)=-47⋅(-53)
Simplify both sides of the equation.
Tap for more steps…
Simplify -47⋅(-7u4).
Tap for more steps…
Cancel the common factor of 4.
Tap for more steps…
Move the leading negative in -47 into the numerator.
-47⋅(-7u4)=-47⋅(-53)
Move the leading negative in -7u4 into the numerator.
-47⋅-7u4=-47⋅(-53)
Factor 4 out of -4.
4(-1)7⋅-7u4=-47⋅(-53)
Cancel the common factor.
4⋅-17⋅-7u4=-47⋅(-53)
Rewrite the expression.
-17⋅(-7u)=-47⋅(-53)
-17⋅(-7u)=-47⋅(-53)
Cancel the common factor of 7.
Tap for more steps…
Factor 7 out of -7u.
-17⋅(7(-u))=-47⋅(-53)
Cancel the common factor.
-17⋅(7(-u))=-47⋅(-53)
Rewrite the expression.
-1⋅(-u)=-47⋅(-53)
-1⋅(-u)=-47⋅(-53)
Multiply.
Tap for more steps…
Multiply -1 by -1.
1⋅u=-47⋅(-53)
Multiply u by 1.
u=-47⋅(-53)
u=-47⋅(-53)
u=-47⋅(-53)
Multiply -47(-53).
Tap for more steps…
Multiply -1 by -1.
u=1(47)53
Multiply 47 by 1.
u=47⋅53
Multiply 47 and 53.
u=4⋅57⋅3
Multiply 4 by 5.
u=207⋅3
Multiply 7 by 3.
u=2021
u=2021
u=2021
The result can be shown in multiple forms.
Exact Form:
u=2021
Decimal Form:
u=0.952380‾
Solve for u -3u+1/3=-5/4u-4/3

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top